Enhancing national security through foreseeing the economic intelligence system in Iraq - Mohammed, Riyadh Fadhel; Ali, Emad Mohammed (Journal of Economics and Administrative Sciences, 2021)
Economic intelligence represents a modern field of knowledge that has been and is still the focus of many studies and research, including this research that deals with economic intelligence and its role in strengthening Iraqi national security - an analytical study. Economic development and economic development without security, and in a situation such as that of Iraq, which is still suffering from conflicts, conflicts and the effects of wars, as well as the unstable conditions in its regional environment, the directions of that relationship cannot be determined except through the availability of accurate information, indicators, full knowledge of reality and the possibility of exploring future possibilities